Associations between teacher academic support and externalizing problem behaviors among Chinese adolescents: an analysis of chain mediation and moderating effects - Zhu, Xingchen; Li, Wencan; Su, Chaoju; Hu, Jinsheng; Zhao, Haohan (Humanities & social sciences communications, 2025)
This research examines how teacher academic support is linked to externalizing problem behaviors in adolescents, providing fresh perspectives on this critical relationship. Although previous studies have looked into the association between teacher support and externalizing behaviors, few have concentrated on the specific impact of teacher academic support on these behaviors. Moreover, aspects like self-education expectations, peer interactions, and parental awareness remain inadequately addressed in the existing literature. In this study, 1011 Chinese adolescents, aged 13 to 17 years, participated in an anonymous self-report survey. The findings reveal that teacher academic support acts as a protective factor against externalizing problem behaviors. Moreover, both self-educational expectations and peer relationships serve as mediators in this relationship. The research also highlights that teacher academic support can indirectly reduce externalizing problem behaviors through the sequential mediation of self-education expectations and peer relationships. Furthermore, parental knowledge is identified as a moderating factor, with the protective effect of teacher support being more pronounced among adolescents with higher levels of parental knowledge. These results underscore the significance of teacher academic support in addressing adolescent externalizing problem behaviors and provide valuable insights for developing effective interventions.